Beatriz González : desplazamientos - Gonzalez, Beatriz, 1938-; Dicker Molano, Mariana; Universidad de Bogotá "Jorge Tadeo Lozano"; Universidad de Bogotá "Jorge Tadeo Lozano". Museo de Artes Visuales (Bogotá, Colombia : Editorial UTadeo, 2019)
The present exhibition and the accompanying texts come from a research-creation project developed by Mariana Dicker, María Alejandra Fajardo, Elkin Rubiano and Javier Gil. This exploration aims to think about the relationships between artistic creation and memory based on Beatriz González's artistic production of the last 20 years. The works of Beatriz González "confirm the possibility that art has to participate in the generation of other narratives, to express the past in another way, to express what is unexpressed in the official history. "Displacements" not only refers to the displaced, or those who are forced to migrate, or the souls who wander waiting for a burial, it also alludes to a series of artistic operations embedded in her creative processes." (HKB Translations) --Page [7].
Presentación -- Beatriz González: Desplazamientos -- Imagen y Memoria / Javier Gil -- Museo/mausoleo: Beatriz González en la búsqueda del duelo / Elkin Rubiano -- Migrantes -- Creación y memoria en Beatriz González / Javier Gil -- Correspondencias -- Todas las mañanas del mundo carecen de retorno / María Alejandra Fajardo -- Catálogo.
Incluye referencias bibliográficas e índice.
In Spanish.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Gonzalez, Beatriz, -- 1938- -- Exhibitions; Gonzalez, Beatriz, -- 1938- -- Criticism and interpretation; González, Beatriz, -- 1938 - -- Exposiciones; González, Beatriz, -- 1938- -- Crítica e interpretación.; Mujeres artistas -- Colombia -- Siglo XX -- Exposiciones; Mujeres artistas -- Colombia -- Siglo XXI -- Exposiciones; Arte colombiano -- Siglo XX -- Exposiciones; Arte colombiano -- Siglo XXI -- Exposiciones; Women artists -- Colombia -- 20th century -- Exhibitions; Women artists -- Colombia -- 21st century -- Exhibitions; Art, Colombian -- 20th century -- Exhibitions; Art, Colombian -- 21st century -- Exhibitions; Libros electrónicos.